MODIFIABLE RISK FACTORS OF PREDIABETES - Khatri Sapkota, Niraj (Innovare Journal of Medical Sciences, 2017)
The presence of prediabetes risk is independently associated with expanded waist circumference or obesity, or investigated laboratory value of low high-density-lipoprotein-cholesterol levels, high triglycerides (dyslipidemia), or measured persistently raised blood pressure (hypertension) and other miscellaneous factors such as eating and drinking habit. Association is stronger in male as compared to female, but abdominal obesity has stringent hold in both sexes to cause prediabetes. Recommendation has to be made on the basis of relative association to prevent or delay the onset of prediabetes to overt Type 2 diabetes; therefore, modifiable factors' recognition and applicatory improvement for the same are necessary. This review attempts to recognize in short of applicable relevant modifiable risk factors of prediabetes.